Reimplantation of an Avulsed Tooth with Extra-oral Dry Time More Than 12 Hours: A Case Report - Chetna Tarnach; Jyotsana Sikri; Aiana Singh; Neha Menrai; Garv Bhargav; Gurinder Singh (Dental Journal of Advance Studies)
Background: Avulsions, which are most frequently observed in the top front teeth, are among the most severe dental injuries. A excellent prognosis is achieved with immediate transplantation of the avulsed tooth, albeit this may not always be feasible. Case study report: The current case illustrates the 1-year follow-up following the delayed (after 16 hours) replantation of a traumatized maxillary central incisor that had been avulsed. Clinical implications and conclusion: In order to preserve the alveolar bone and assist the patient psychologically, delayed replantation of an avulsed tooth may be a good option to prosthesis. Additionally, initiatives should be taken to inform and educate the public on the care of avulsed teeth at accident scenes and dentist offices.